Mengenal Aksara Bali: Balinese Script game education based on mobile application - I Gede Andika; Daniel Eka Saputra; Christina Purnama Yanti; Gede Indrawan (Journal of Games, Game Art, and Gamification, 2019)
Balinese Scriptwriting, as one of Balinese cultural richness, is going to extinct because of its decreasing use. Governor of Bali, I Wayan Koster, expressed concern about the increasingly diminishing interest of the community, especially among the younger generation using it. This research focused on the development of a Balinese Script game education based on a mobile application called Mengenal Aksara Bali. In this research area, Mengenal Aksara Bali offered a solution as an application that is not only for playing,but also provided features for learning Balinese Script glyphs (Aksara Wresastraand numbers). Mengenal Aksara Bali was implemented by using Construct2(a powerful game creator designed especially for 2D games). Through Black Box testing, its functions in the application wasrunning as expected